THE URGENCY OF LEGAL PROTECTION FOR SOLVENT COMPANIES WITH GOOD INTENTIONS IN BANKRUPTCY LAW IN INDONESIA - Ketut Suryadinata Putra; Marwanto Marwanto (Transpublika Publisher, 2024)
Bankruptcy is a situation when the debtors are unable to fulfill their obligations to pay debts to creditors. The requirement for a bankruptcy decision is based on Article 2 paragraph (1), namely that the debtors have two or more creditors and have not paid in full at least one debt that has matured and can be collected. This causes no legal protection for debtor companies that are still solvent and have good intentions from creditors who have bad intentions in abusing bankruptcy law. The debtors with good intentions will certainly find it difficult to face a bankruptcy application if the conditions are only 2+1. Debtor companies that do not pay off their debts do not always have bad intentions but face the threat of bankruptcy which should not be aimed at them. The study aims to understand how Indonesian bankruptcy law can better protect financially stable companies with good intentions from being unfairly declared bankrupt. This research used normative legal research using primary and tertiary legal materials collected from literature and document studies and analyzed qualitatively. The results of this research showed that legal protection and justice can be given to solvent debtors who have good intentions if bankruptcy law in Indonesia provides regulations regarding insolvency tests as an instrument to prove factually whether the debtor's financial condition is still healthy (solvent) or unhealthy (insolvent) so that it is appropriate to sentenced to bankruptcy.